Greece : Staff Report on Request for Stand-By Arrangement. (IMF Staff Country Reports; Country Report ;, 2010)
The Greek economy is teetering owing to heavy public debt and loss of market access. Greece is adopting an ambitious comprehensive multiyear adjustment program to lower the fiscal deficit and the debt ratio, reduce domestic demand in line with capacity, and increase supply and competitiveness so that the economy can step onto a higher growth path led by investments and exports. Greece needs a strong and sustained adjustment program to lower the fiscal deficit substantially and create the basis for a declining debt ratio.